2019
DOI: 10.21608/ejss.2019.17427.1310
|View full text |Cite
|
Sign up to set email alerts
|

Indirect estimation of deep percolation using soil water balance equation and NASA Land Simulation Model (LIS) for more sustainable water management

Abstract: Sustainable management to water resources involves precise estimation for groundwater recharge. The better understanding of the estimated amount of deep percolation and behavior would contribute to more sustainable water resources planning. Soil water balance (SWB) equation computes deep percolation (DP) precisely if adequately applied. Lysimeters are efficient instruments used to compute each component of SWB model with high accuracy. This method is very sophisticated and costs A CCURATE estimation for ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is characterized by imperfect to well-drained soil as it was formed within the alluvium of the Nile delta, which has been deposited in semiarid climates [66]. The hydrology of the area is affected by both the River Nile irrigation canals, and the seepage from the Mediterranean Seawater, but overall, the groundwater quality of the area is mostly good [66][67][68]. The natural environments in the region can be classified into three main types: agricultural and urban environments, coastal environments, and wetlands.…”
Section: Methodsmentioning
confidence: 99%
“…It is characterized by imperfect to well-drained soil as it was formed within the alluvium of the Nile delta, which has been deposited in semiarid climates [66]. The hydrology of the area is affected by both the River Nile irrigation canals, and the seepage from the Mediterranean Seawater, but overall, the groundwater quality of the area is mostly good [66][67][68]. The natural environments in the region can be classified into three main types: agricultural and urban environments, coastal environments, and wetlands.…”
Section: Methodsmentioning
confidence: 99%
“…These results are similar to those in some studies. Elbana et al (2019) [90], who concluded that higher rates of deep percolation could be found in the loose soil with low slope. Omulabi et al (2000) [65] studied the influence of soil physical properties on infiltrations rates of sand, clay and silt concluded that infiltration rates varied significantly between the three.…”
Section: Discussionmentioning
confidence: 99%
“…Such task was not adopted because our objectives were the full curve determination and a comparison of the equations based on similar conditions. Therefore, the models required special measurements of soil properties, and the models with technical disadvantages were considered out of the comparison (El-Nady, 2015 andElbana et al, 2019).…”
Section: Many Different Equations Have Been Developedmentioning
confidence: 99%
“…2-6 and appendix A). In this respect, Elbana et al (2019) suggested conducting further studies in different agro-ecological areas in Egypt to optain more precise model calibration and validation. The PE was tested based on actual measurements of the SWCC between 0 and 1500 kPa suction for a clay soil (Fig.…”
Section: Measured Data Of Swccs and Pementioning
confidence: 99%